The Potential of Blockchain within Air Rights Development as a Prevention Measure against Urban Sprawl - Zaheer Allam; David Sydney Jones (Urban Science, 2019)
The rapid rise in urbanization internationally is both driving and stressing our consumption patterns, including that of land use. Urban sprawl is arguably one of the most important threats to human and nature biodiversity given its reliance upon fossil fuel exploitation and consumption. The need for increasing the density of cities is required to contain urban expansion in land size. However, while the footprint density of cities is increasing, vacant plots are prized and rare in most urban areas. Tradable air rights development is seen as a potential solution to provide developers the option of increasing density while encouraging an emerging urban economy. However, the price speculation of air rights is a danger and counter to a fair and inclusive real estate market. This paper proposes a new model that encourages the trading of time-sensitive air rights through Smart Contracts in the Blockchain as a means of prevention against urban sprawl.